2020
DOI: 10.3340/jkns.2019.0220
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between E-Selectin S128R Gene Polymorphism and Ischemic Stroke in Chinese Population : A Meta-Analysis

Abstract: To perform a systematic review of the data collected from case-control studies conducted earlier to investigate the correlation between E-selectin S128R polymorphism and ischemic stroke (IS) risk among the Chinese population. The PubMed, Web of Science, Chinese biomedical literature database (CBM), Chinese databases China National Knowledge Infrastructure (CNKI), WanfangData knowledge service platform (Wanfang Data), and information resource integration service platform (VIP) Databases were searched to retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Yet, these SNPs have been found to be associated with other pathologies also involving the endothelial dysfunction. For example, it has been reported that the R allele and the RS genotype in E-selectinS128R may be associated with the increased risk of ischemic stroke in Chinese, Asian, African, and Caucasian populations [26,27]. Wang X, et al [28] suggested that theS128R polymorphism may be associated with the increased risk of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these SNPs have been found to be associated with other pathologies also involving the endothelial dysfunction. For example, it has been reported that the R allele and the RS genotype in E-selectinS128R may be associated with the increased risk of ischemic stroke in Chinese, Asian, African, and Caucasian populations [26,27]. Wang X, et al [28] suggested that theS128R polymorphism may be associated with the increased risk of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%